AB0957 Is there a difference in the clinical presentation of juvenile systemic scleroderma patients according the age of onset: results from the juvenile scleroderma inception cohort www.juvenile-scleroderma.com. (15th June 2017) - Foeldvari, I; Klotsche, J; Kasapçopur, O; Adrovic, A; Stanevicha, V; Terreri, MT; Alexeeva, E; Katsicas, M; Smith, V; Cimaz, R; Kostik, M; Lehman, T; et al.
Abstract : Background: Juvenile systemic sclerosis (jSSc) is an orphan autoimmune disease. It was rarely looked at the differences between the clinical presentations of patients at different paediatric age groups. The juvenile scleroderma inception cohort (www.juvenile-scleroderma.com) is a prospective standardized register for patients with jSSc. Objectives: Comparison of clinical characteristics of patients with different age range at the time of inclusion in the registry. Methods: Patients with jSSc were included worldwide to the juvenile scleroderma inception cohort. We compared the demographics and clinical characteristics of the patients at different age ranges. We created 3 cohorts with different age ranges at onset of disease. Patents aged less than 5 years (Group1), 5–10 years (Group2) and over 10 years (Group3) at the time of diagnosis of the first non-Raynaud involvement of jSSc. Results: Up till now 88 patients were enrolled, 14 patients (15%) in Group1, 22 (25%) in Group2 and 52 (59%) in Group3. Diffuse subtype occurred in 71% in Group1, in 82% in Group2 and in 65% in Group3. Most patients were Caucasian. Disease duration at time of inclusion into the cohort was 3.9 years in Group1, 4.9 years in Group2 and 2.2 years in Group3. ANA positivity was 57% in Group1, 77% in Group2 and 86% in Group3. Anti-scl 70 was around 30% in all groups. Anti-Centromere positivity was 7 to 10%. Mean modified skin score was 12.4 in Group1, 16.5 in Group2 and 15.9 in Group3. Raynaud Phenomenon occurred in 85 to 95% of the patients. History of active or inactive ulceration occurred in 57% in Group1, 62% in Group2 and 43% in Group3. Decreased FVC under 80% occurred in 43% in Group1, 32% in Group2 and 30% in Group3. Pulmonary hypertension occurred in 7% in Group1 and in 10% in Group3. No renal hypertension was observed. Urinary sedimentary changes occurred in 7% in Group1 and in 10% in Group3. Gastrointestinal involvement occurred in 21% in Group1, 45% in Group2 and 27% in Group3. Musculoskeletal involvement occurred in 58 to 64%. Patient global disease activity (VAS 0–100) was 42.8 to 47.9. Patient global disease damage (VAS 0–100) was 39.6- to 45.0. Physician global disease activity (VAS 0–100) was 35.4–40.0. Physician global disease damage (VAS 0–100) was 37.1 in Group1, 41.3 in Group2 and 27.7 in Group3. Conclusions: It seems to be that patients, with onset of the disease in younger age have more severe disease as patients with disease onset after the age of 10 years. We need more patients in our cohort to gain more sufficient data to prove our preliminary observation. Disclosure of Interest: None declared